CryoTransmission Electron Microscopy a reliable technique or just another expensive attachment - Azinuddin Zulfahmi, Megat (2020)
The skinny Science Officer lifted the 5-litre cryogenic Dewar tank and poured the minus 192-degree Celsius liquid into a black apparatus on the cabinet. Huffing and puffing, he carefully managed to fill up the rounded shape apparatus to the brim. Both Dewar and the black thing is known as the cryo specimen holder shoots up cold nitrogen vapour, producing layers of fogs on his spectacle. A Smartest heater controller connected to a mini Dewar tank measure the temperature.